(untitled) (Torani Journal of Fisheries and Marine Science, 2025)
A leading commodity that has the potential to be developed as an export commodity for Indonesia is seaweed. One type of Gracilaria that has economic value and is widely cultivated is Gracilaria verrucosa. This study aims to analyze the effect of nitrogen (N) and phospor (P) concentration ratio on carbohydrate and lipid content in G. verrucosa seaweed cultivated outdoors. This research was conducted in May-June 2023 at the Hatchery FIKP, Hasanuddin University. Seaweed seedlings were reared for 44 days using 70 cm diameter conical fiber tanks filled with 100 g/150 L of water. This study used a non-parametric method Kruskal-Wallis consisting of 3 treatments and each treatment consisted of 3 replicates so that there were 9 experimental units. Based on the results of Kruskal-wallis analysis showed significant differences in carbohydrate content in seaweed G. verrucosa). The highest carbohydrate content was obtained in the treatment with a ratio of 2 ppm : 1 ppm (A), which is 33.49%, treatment with 2 ppm : 1.5 ppm (B) is 29.56% and the lowest treatment was in the ratio of 2 ppm: 2 ppm (C) which is 29.28%. The highest lipid content was at a ratio of 2 ppm: 2 ppm (C) 0.84% and the lowest at a ratio of 2 ppm: The water quality parameters observed during the study were all suitable for the growth of G. verrucosa.